2017
DOI: 10.15406/ijcam.2017.05.00167
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic Treatment of Infertility: A Medical and Bioethical Perspective

Abstract: Homoeopathy has a significant clinical history, tracing its roots back to the ancient physician Hippocrates. In the last 30 years, it has surged in popularity among those seeking alternative forms of medical treatment. Countering this increase in popularity, some recent meta-analyses have suggested that the therapeutic claims of homeopathy lack scientific justification. A popular area of homeopathic application is infertility. In this paper we review the homeopathic approach and the bioethical implications to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…Here is a case of secondary infertility, successfully treated with evidence based Homeopathic medicine showing the usefulness of homeopathy in the management of infertility due to PCOS. Anit a lu et al [10] shown effectiveness of homoeopathy in treatment of PCOD with infertility Homoeopathic constitutional remedies were successful in treating 17 out of 20 PCOD cases testing positive for Urine Pregnancy Test and USG of pelvis. Role of homoeopathy in the management of PCOS and infertility has been well reported in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Here is a case of secondary infertility, successfully treated with evidence based Homeopathic medicine showing the usefulness of homeopathy in the management of infertility due to PCOS. Anit a lu et al [10] shown effectiveness of homoeopathy in treatment of PCOD with infertility Homoeopathic constitutional remedies were successful in treating 17 out of 20 PCOD cases testing positive for Urine Pregnancy Test and USG of pelvis. Role of homoeopathy in the management of PCOS and infertility has been well reported in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Successful results can be obtained from homeopathic treatments in cases where conventional medical methods are inadequate or unsuccessful in the treatment of infertility, or in couples who want to avoid the side effects of operative and hormonal treatments [4,5,6].…”
Section: Introductıonmentioning
confidence: 99%
“…Literature review in Homoeopathy revealed studies [13][14] and case reports [15][16] in which uterine fibroids had been treated successfully with homoeopathic medicine. It also had been shown in the review article of 'Homeopathic treatment of infertility: A medical and bioethical perspective', the author has observed the homoeopathic approach and the bioethical implications to infertility and proposed that monitoring the effects of homoeopathic remedies on infertile women may be an effective method to assess the efficacy of this form of alternative medicine [17] Here, I presented a case of secondary infertility in a female with having UF who was long been treated with modern medical therapies but no spontaneous conception had been achieved and finally she was advised for surgery. For avoiding the surgery she attended to Out Patient Department of Dr. Anjali Chatterjee Regional Research Institute for Homoeopathy [(DACRRI)-H], Kolkata for Homoeopathic treatment.…”
Section: Introductionmentioning
confidence: 99%